DURATION IN HARRY POTTER AND THE DEATHLY HALLOWS - Wardhana, Wisnu Putra (Program Studi Sastra Inggris, Fakultas Sastra, Universitas Komputer Indonesia Bandung, 2018)
This research is regarding narrative in Harry Potter and The Deathly Hallows. Narrative has many ways to develop the narrative. One of them is duration. There are five possibilities, which suggest themselves. They are summary, ellipsis, scene, stretch and pause. In each possibility, they have different use of time. Qualitative method and descriptive analysis are used to analyze the data. The data are taken from Harry Potter and The Deathly Hallows. The theory used in this research is from Seymour Chatman (1978). Summary occurs when the time is cut short in story-time, complemented with durative verb and adverb. Ellipsis is happened when the discourse in the story is stopped yet the story-time keeps on going, abridging the story-time to the period which is already determined. Scene happens when the story-time and discourse-time run together using dialogue and overt physical actions of relatively short duration. Stretch is happened when discourse-time runs longer than story-time, using imagination to cut short the story-time and enter the discourse time. Pause is occurred when the story-time stops completely and discourse-time takes over, describing the event or characters.